Cervical cancer screening utilization, and associated factors, in Nepal: a systematic review and meta-analysis. (September 2022) - Shrestha, A.D.; Andersen, J.G.; Gyawali, B.; Shrestha, A.; Shrestha, S.; Neupane, D.; Ghimire, S.; Campbell, C.; Kallestrup, P.
Abstract: Objective: To systematically appraise the existing published literature on cervical cancer screening utilization, and associated barriers and facilitators, in Nepal. Study design: Systematic literature review and meta-analysis. Methods: PubMed/MEDLINE, CINAHL, Scopus, Embase, and, Google Scholar were systematically searched using Preferred Reporting Items for Systematic Review and Meta-Analysis guideline. All quantitative and qualitative studies reporting cervical cancer screening (using the Pap smear test or visual inspection with acetic acid or human papillomavirus test) utilization, barriers, and facilitators for screening were identified. A meta-analysis was performed to estimate Nepal's pooled cervical cancer screening utilization proportion. Results: The search yielded 97 records, of which 17 studies were included. Fifteen studies were quantitative and two were qualitative. Of the 17 studies, six were hospital-based and six were community-based. The pooled cervical cancer screening utilization proportion (using Pap smear test) among Nepalese women was 17% from the studies in the hospital settings, and 16% in the community. Six studies reported barriers to cervical cancer screening, of which four reported embarrassments related to the gynecological examination and a low level of knowledge on cervical cancer. Three (of four) studies reported health personnel, and two studies reported screening services–related facilitators for cervical cancer screening. Conclusion: Our review reported that cervical cancer screening utilization (16%) is more than four times lower than the national target (70%) in Nepal. Multiple barriers such as low levels of knowledge and embarrassment are associated with cervical cancer screening utilization. Health personnel's gender, counseling, and privacy of screening services were commonly reported facilitators. These findings could help to inform future research, and policy efforts to increase cervical cancer screening utilization in Nepal.